Overexpression MsJAR1 gene increased lateral branches and plant height in alfalfa (Medicago sativa L.) - Rui Dai; Qi Chen; Xiao-yu Wang; Xiao-wei Huo; Jian-wei Li; Jiang-bo An; Fu-gui Mi; Feng-ling Shi; Zhi-qiang Zhang (Scientific Reports)
Abstract Alfalfa (Medicago sativa L.) is an important legume forage known for its high yield, quality, and adaptability. However, due to its cross-pollination and tetraploid inheritance characteristics, biotechnologies such as genetic modification and gene editing are challenging to be utilized in the practice of alfalfa breeding. In this study, a MsJAR1 gene involved in jasmonic acid (JA)pathway was overexpressed into ‘Zhongmu No.1’ alfalfa, and the effects of MsJAR1 gene on alfalfa development were analyzed. Subcellular localization results indicated that the MsJAR1 protein was located to chloroplast. Compared to wildtype (WT), MsJAR1 overexpressed alfalfa plants displayed smaller leaves, reduced internode distance, increased lateral branches and plant height. Moreover, anatomical analysis revealed that xylem and phloem area decreased in leaves but increased in stems of MsJAR1 overexpressed alfalfa. Except intercellular CO₂, photosynthetic rates, stomatal conductance, and transpiration were significantly higher than in MsJAR1 overexpressed alfalfa. Comparative transcriptomics results showed that 12,046 DEGs were identified between transgenic alfalfa (OE-1 and OE-2) and WT. The DEGs were significantly enriched in ribosome, glycolysis / gluconeogenesis and tricarboxylic acid cycle pathways. Therefore, it is speculated that the MsJAR1 gene affects the growth and development of alfalfa by regulating photosynthesis-related pathways.